ERRORS ANALYSIS IN PASSIVE VOICE AT UNDHIRA STUDENTS’ THESES AGREED FOR FOLLOWING THE FINAL COMPREHENSIVE TEST - I Gusti Nyoman Putra Kamayana (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2021)
ABSTRACTThis article is part of the writer’s study on the grammatical error analysis. It is the studyon students’ theses as the final academic projects for getting the bachelor degree at EnglishDepartment of Universitas Dhyana Pura Bali. The students were allowed for joining finalcomprehensive test, to write their studies by using right grammar. However, they still wroteerrors writing. Propose of this study identified the types and percentage of grammaticalerrors in using passive voice. It was made by the students in their writing products in termsof studies agreed by their advisors for following the final comprehensive test. This study wasdone by applying descriptive research design. The total member of this study was thedocuments in the form of 30 students’ studies. They were agreed for following the finalcomprehensive test in three periods of final comprehensive tests from 2018/2019 up to2020/2021. Random sampling technic was made use of collecting 3 studies (about 10% ofthe population) as the sample. In getting the data, researcher read and analyzed all of 3students’ studies. It was found that the students wrote errors in using passive voice in eachtypes of surface strategy taxonomy. The highest level of the grammatical errors on passiveusage in on “Omission” type. The omission in preposition, to be, conjunction, and verbal. Itindicated that the students still have got problem in using passive voice. The lecturers ofgrammar are suggested to pay more attention and consider the appropriate teachingtechnique in teaching in passive voice. This study is also recommended to students’ advisorsto give more checking on the students’ errors for the accompaniment process of theirstudents’ errors, particularly in making use of passive voice.Kata kunci: grammatical error analysis, passive voice, students’ theses.